Morphological variation in Xenoxybelis boulengeri (Procter, 1923) (Serpentes, Xenodontinae, Philodryadini) - Da Costa Prudente, Ana Lúcia; Da Silva, Márcio André Amorim; Da Rocha, Wáldima Alves; Franco, Francisco Luís (Zootaxa, 2008)
The genus Xenoxybelis contains two species, X. argenteus and X. boulengeri, characterized by semi-arboreal habits and an extremely thin rostral area, classified in the subfamily Xenodontinae (Colubridae). Xenoxybelis boulengeri is considered a rare species and is poorly represented in scientific collections. Its external morphology is known only from the original description and seven other specimens. In this study, twenty additional specimens were examined from the Brazilian states of Acre, Amazonas and Rondônia. Variation in meristic and morphometric characters are described, and new characters are incorporated in a revised diagnosis of the species. Illustrations and a description of the hemipenes of X. boulengeri are presented for the first time. Analysis of morphological and molecular characters permit allocation of Xenoxybelis to the tribe Phylodryadini, together with Ditaxodon, Philodryas, Pseudablabes and Tropidodryas.